TEACHING ONLINE LISTENING CLASS DURING COVID-19 PANDEMIC - Endang Setiyo Astuti; Rini Anjarwati (Unit Pengembangan Bahasa UIN Sayyid Ali Rahmatullah Tulungagung, 2021)
This article discusses about how teaching listening class was implemented in the English practice program during covid-19 pandemic. Descriptive method was applied to find out whether selected material utilized by effective instructional media could meet the learning objective of the English practice program. The result showed that both the intensive and extensive material in listening class could be applied by using some media that can be used during online class by considering both students and instructors’ internet access. The selected online media platform that can replace face-to-face meeting is Google Meet application, while Google Classroom, YouTube, and WhatsApp application are selected to share and submit the class’s assignments. The teacher’s role in engaging the students with particular activities are highlighted.